Overwintering Locations, Migrations, and Fidelity of Radio-Tagged Dolly Varden in the Hulahula River, Arctic National Wildlife Refuge, 2007–09 - Brown, Randy J.; Loewen, Mary Beth; Tanner, Theresa L. (ARCTIC, 2014)
Essential overwintering habitats for anadromous Dolly Varden Salvelinus malma on Alaska’s North Slope appear to be limited to a small number of perennial springs, primarily in eastern Brooks Range drainages. Because future petrochemical development in the region continues to be a possibility, and development would require large quantities of freshwater, we sought to identify and document the overwintering areas used by Dolly Varden in the Hulahula River, eastern Brooks Range. In August 2007, we implanted 52 Dolly Varden with multi-year radio transmitters at a known overwintering area in the lower Hulahula River. Other wintering areas were located during 11 aerial surveys conducted over the next 2.5 years. A stationary receiver located in the lower Hulahula River provided migration timing information. Radio-tagged Dolly Varden used four discrete areas with perennial springs for overwintering in the Hulahula River drainage. The springs, totaling approximately 12 km in stream length, were located between river km 40 and 105. Radio-tagged Dolly Varden migrated downstream on their way to the Beaufort Sea in early June. Most tagged fish known to have survived the summer at sea returned to the Hulahula River during late July and August, but seven fish overwintered in other North Slope drainages. Within the Hulahula River drainage, 15 fish overwintered in more than one area during the three winters of the project, but only the four identified perennial spring areas were used. These data clearly indicate that the perennial springs in the Hulahula River are essential overwintering habitats for Dolly Varden. Les aires de concentration hivernales essentielles du Dolly Varden Salvelinus malma anadrome sur la North Slope de l’Alaska semblent limitées à un petit nombre de sources pérennes, principalement dans les bassins hydrographiques de l’est de la chaîne de Brooks. Puisqu’il est toujours possible qu’il y ait des aménagements pétrochimiques dans la région et que ceux-ci demanderaient de grandes quantités d’eau douce, nous ...